(untitled) (CIPEEX, 2025)
OBJECTIVE: The article aims to investigate the influence of fake news on voter behavior during the electoral process, addressing the clash between freedom of expression and misinformation, the limits of the actions of the Superior Electoral Court (TSE), and the challenges in regulating social networks. The so-called fake news, or false news, have the potential to exert significant influence on voter behavior during election periods. The rapid and extensive spread of this type of misleading information, especially on social media, can alter voters’ perceptions of candidates, parties, and political issues, compromising the integrity of elections and trust in democratic institutions. INTRODUCTION: The phenomenon of spreading incorrect or misleading information, with the aim of influencing the citizen’s decision-making process and shaping public opinion, has played a significant role in various electoral campaigns and political events over the past few years (BITENCOURT, Maryana Espíndola, 2023). Various studies have demonstrated the danger that misinformation represents by impacting the credibility of traditional institutions, the State, and society. METHOD: The study uses a literature review, documentary analysis of TSE decisions and resolutions, and case studies of the Brazilian elections of 2018 and 2022. RESULTS: The present study indicates evidence of a direct impact of fake news on the electoral process. During the 2018 election, there was a massive dissemination of false information, mainly thru the WhatsApp application, which undermined trust in the electoral system and diverted the focus from political debate. Similarly, in the 2022 elections, false news, such as allegations of fraud in electronic voting machines, continued to negatively influence voters’ perception of the integrity of the electoral process. New technologies brought significant benefits to democracy. They also intensified polarization, political radicalization, and the intentional spread of misinformation, threatening constitutional values such as popular sovereignty and equality in public debate. Freedom of expression is a fundamental and essential right for the exercise of democracy. In the context of elections, freedom is the essence of a democratic state; it enables people to express their expectations and exercise their right to vote. The TSE has been working to suppress abuses, applying electoral legislation and the General Data Protection Law (LGPD) to combat the dissemination of fraudulent content. CONCLUSION: Misinformation represents a significant risk to democracy, requiring coordinated responses between the State, social networks, and society. Freedom of expression must be preserved, maintaining the balance between the free manifestation of thot and the integrity of the electoral process. The TSE, within its constitutional limits, plays a crucial role in this confrontation, and its actions must be guided by due process and respect for the adversarial system. Transparency in the electoral process is a relevant factor to ensure the population’s trust in the democratic system and the right to vote. Studies indicate that the promotion of verified information and plural debate are essential elements to mitigate the effects of informational manipulation and harmful interactions in the virtual environment.